18.4k views
3 votes
Ŵhat is the answer to this? Or any help please :)
2x+3y=13
4x-y=-2

User FurkanO
by
5.1k points

2 Answers

3 votes

Answer: x=1/2 and y=4

Explanation:

There are two ways to go about this problem.

1. Substitution

2. Elimination

Substitution Method:

rearrange one of the equations so that it is in terms of a variable. I will rearrange the bottom equation which is 4x-y=-2 which can also be written as y=4x+2

Now we will plug that value of "y" into the first equation and get 2x + 3 *(4x+2)=13

Now we will solve for x

2x +12x+6=13

14x=7

x=7/14 or 1/2

Plug x into the the equation and solve for y

2(1/2) + 3y=13

3y=12

y=4

Check your answer by plugging both in to the second equation

4(1/2)-4=-2?

2-4=-2

-2=-2

Elimination Method:

In order to eliminate a term you need to have an x or y term that is equal or opposite so we can subtract or add both equations together. To do this we will multiple the top equation by a factor of 2 and end up with: 4x+6y=26

Now we are going to subtract the bottom equation from the top

4x+6y=26

-

4x-y=-2

7y=28

y=4

Plug in to get x

4x-4=-2

4x=2

x=2/4 or 1/2

Check!

2(1/2) + 3(4) = 13?

1+12=13

13=13

User Wendell
by
5.6k points
0 votes

X = 0.5 and Y = 4.

Hope this helps you hun

User Dvanderb
by
5.4k points